2022
DOI: 10.1007/s10896-021-00345-7
|View full text |Cite
|
Sign up to set email alerts
|

Growing Up with Intimate Partner Violence at Home: Adolescents’ Narratives on Their Coping Strategies

Abstract: Purpose The research on adolescents who have grown up around intimate partner violence (IPV) between their parents or caregivers has mostly focused on adolescent’s victimization experiences and the negative impact of this type of violence on their mental health. More research is needed on how they respond to these experiences. The aim of this study is to understand adolescents’ coping strategies regarding IPV between their parents or caregivers, from their perspectives. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…CEIPV studies, which include YP, often portray them as being defined by harmful experiences lived in childhood and damaged witnesses to violence (Adhia et al, 2019;Whatley, 2019), failing to explore the meanings of or responses to such experiences. As a result, these gaps in the literature prevent a complete understanding of the nuances and complexities of CEIPV (Miranda et al, 2023). Furthermore, a recent meta-synthesis which looked at the nature and extent of qualitative research conducted in the last two decades with children about their CEIPV confirmed that they did not have adequate opportunities to talk, be listened to, and taken seriously (Noble-Carr et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…CEIPV studies, which include YP, often portray them as being defined by harmful experiences lived in childhood and damaged witnesses to violence (Adhia et al, 2019;Whatley, 2019), failing to explore the meanings of or responses to such experiences. As a result, these gaps in the literature prevent a complete understanding of the nuances and complexities of CEIPV (Miranda et al, 2023). Furthermore, a recent meta-synthesis which looked at the nature and extent of qualitative research conducted in the last two decades with children about their CEIPV confirmed that they did not have adequate opportunities to talk, be listened to, and taken seriously (Noble-Carr et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Domestic violence has a very bad effect on children (Ragavan et al, 2018). As for children who are raised in families or environments that experience domestic violence, they will experience stunted development, for example in terms of social maturity (Miranda et al, 2022). Children will tend to find it difficult to develop feelings of peace and calm, will always feel afraid, find it difficult to interact with other people, and tend to be more aggressive when playing with their peers (Lamela et al, 2021).…”
Section: Introductionmentioning
confidence: 99%